The State Canonization of Mazu: Bringing the Notion of Imperial Metaphor into Conversation with the Personal Model - Zhang, Yanchao (Religions, 2019)
Drawing from Stephan Feuchtwang's influential notion of "imperial metaphor," this article explores the role that the state played in the development of the Mazu cult in late imperial China. I argue that the state was central in the canonization of Mazu, elevating her from a polyvalent local object of devotion to a key deity in a national cult that strongly reflected official ideology. State canonization involved three deeply intertwined strategies to standardize, give public recognition, and promote a range of local beliefs and practices: the conferral of official titles, the incorporation of local gods and goddesses into the register of sacrifices, and the construction of official temples. As a result of these interwoven processes, Mazu became associated with domestic defense and warfare, the protection of government officials, and the involvement in political endeavors. As such, the imperial version of goddess worship served to justify and reinforce imperial authority. For all the analytical strength of the notion of imperial metaphor, I contend, however, that it needs to be supplemented with and critiqued by Robert Hymes' "personal model," in order to fully understand the complexity and dynamism of the Mazu devotion, and more generally, of popular religion in late imperial China.